Entre la participación ciudadana y las resistencias creativas: Una experiencia en la localidad de Engativá (2013)
This article examines the relation between arts and politics. It’s based on the resultsof a sociological research purposed to understand the local political culture throughthe social practices and representations in the Local Council of Culture, during thenegotiation, formulation, implementation and assessment processes of political cultures in the locality of Engativa, Bogota, Colombia; all these from the experience of the group Viajeros del Arte (Travelers in the Art), colective action of local artists in response to the bad government, and aimed to dignify the artistic performances.